Application of X-ray diffractometry and simultaneous thermal analysis for studying the phase composition of barium ferrites - Bobuyok, S. A.; Surzhikov, A. P.; Nikolaev, E. V.; Vlasov, V. A.; Lysenko, E. N. (Russian physics journal, 2025)
Unsubstituted and complex substituted barium ferrites of a magnetoplumbite structure of the following compositions: BaFe 12 O 19 , BaFe 11.8 Al 0.2 O 19 , BaZn 0.2 Zr 0.2 Fe 11.6 O 19 and BaZn 0.2 Zr 0.2 Al 0.2 Fe 11.4 O 19 are studied. The main focus is on their phase compositions and magnetic phase transitions within the Curie temperature interval. The common patterns of variation in the ferrite crystal lattice volume as a function of the substituting cation sizes are revealed. During a simultaneous thermal analysis in the magnetic field, a correlation is observed between the instrumental variation of the sample weight and the changes of their heat capacity in the Curie temperature region. It is found out that the temperature range of the magnetic phase transition increases with the increasing content of the elements substituting iron atoms, while the Curie temperature decreases. It is shown that a thermal analysis allows effectively separating the phases in the mixture of composite powders of BaFe 12 O 19 —BaZn 0.2 Zr 0.2 Al 0.2 Fe 11.4 O 19 , not possible using X‑ray diffraction due to very small differences in the crystal lattice parameters of these two ferrite phases, causing an overlapping of their peaks in the XRD pattern. The results of this study emphasize the importance of using the simultaneous thermal analysis during the examination of phase compositions of multicomponent magnetic materials.